Pedomonas mirosovicensis gen. nov., sp. nov., a bacterium isolated from soil with the aid of Micrococcus luteus culture supernatant containing resuscitation-promoting factor. Issue 8 (5th August 2022) - Lopez Marin, Marco A.; Suman, Jachym; Jani, Kunal; Ulbrich, Pavel; Cajthaml, Tomas; Pajer, Petr; Wolf, Jacqueline; Neumann-Schaal, Meina; Strejcek, Michal; Uhlik, Ondrej
Abstract : An orange-golden iridescent culture, designated A1X5R2 T, was isolated from a compost soil suspension which was amended with Micrococcus luteus NCTC 2665 T culture supernatant. The cells were non-motile, Gram-stain-negative, 0.4–0.5 µm wide and 0.7–1.4 µm long. The 16S rRNA-based phylogenetic and whole-genome analyses revealed that strain A1X5R2 T forms a distinct lineage within the family Sphingosinicellaceae and is closely related to members of the genus Sphingoaurantiacus ( S. capsulatus, 93.04 % similarity, and S. polygranulatus, 92.77 %). The organism grew at 22–47 °C (optimal at 37 °C), salinity <3 % (optimal at 1.5 %) and at pH 7. The major respiratory quinone was ubiquinone-10, but a small quantity of ubiquinone-9 was also detected The major polyamine was homospermidine, but a small quantity of putrescine was also detected. The strain contained C18  :  1 ω7 c, C16 : 0, C16 : 1  ω7 c and C18 : 0 as the major fatty acids. The main polar lipids were phosphatidylethanolamine, phosphatidylglycerol, phosphatidylcholine, phosphatidylinositol, sphingoglycolipid, diphosphatidylglycerol, two unidentified phospholipids and three unidentified amino lipids. The DNA G+C content was 64.9 mol%. According to the results of phylogenetic and phylogenomic analyses, as well as its physiological characteristics, strain A2X5R2 T represents the type species of a novel genus within the family Sphingosinicellaceae . The name Pedomonas mirosovicensis gen. nov., sp. nov. is proposed, with the type strain being A1X5R2 T (=NCCB 100839 T =DSM 112829 T ).